Comparison of three biomass-based carbon-negative power generation systems. (20th February 2021) - Yan, Linbo; Wang, Luchao; Wang, Ziliang; Cao, Yang; He, Boshu
Abstract: With the advent of a series of science and policy concerns about global warming, attention has been paid on clean power generation with low or even negative CO2 emission. Bioenergy with carbon capture and sequestration technologies can produce heat and power whilst removing CO2 indirectly from air, but it suffers low energy efficiency and poor economy. To improve the performance so that it can be practically used in industry, a series of research is done in this work. A bioenergy with carbon capture and sequestration superstructure is put forward. Three representative schemes, including a biomass-fired power plant, a biomass-fueled integrated gasification combined cycle and a biomass-fueled integrated gasification fuel cell system are constructed and compared thermodynamically with the assistance of the commercial software Aspen Plus. It is found that the net electric efficiencies of the biomass-fired power plant, the biomass-fueled integrated gasification combined cycle and the biomass-fueled integrated gasification fuel cell are 30.7%, 44.5% and 50.5%. The electric power generation per unit biomass consumption of the three systems can be 1.37 kWh/kg, 1.98 kWh/kg and 2.31 kWh/kg. The costs of electricity produced by the three systems are 0.0584 /kWh, 0.0497 /kWh and 0.0493 /kWh. The CO2 mitigation rate per unit power generation of the three systems can be 0.943 kg/kWh, 0.629 kg/kWh and 0.567 kg/kWh. All these findings indicate that the biomass-fueled integrated gasification fuel cell system is promising for future clean power generation with negative CO2 emission. Graphical abstract: Image 1 Highlight: Three representative BECCS systems are constructed and systematically modeled. The BECCS sub-unit models are validated thermodynamically and economically. Efficiencies of BFPP, BIGCC and BIGFC are 30.7%, 44.5% and 50.5%. Electric costs of BFPP, BIGCC and BIGFC are 0.0584, 0.0497 and 0.0493 /kWh. CO2 mitigations of BFPP, BIGCC and BIGFC are 0.943, 0.629 and 0.567 kg/kWh.